Principal’s Leadership in Building Student’s Character - Saputra, Firman (PPSDP International Journal of Education, 2023)
The purpose of this study is to evaluate how the vision, mission, and tactics for SMA Negeri 3 Kayuagung students’ character education are being put into practice. This study employed a qualitative methodology. Interviews, observation, and documentation were employed as the data collection methods. The first study’s findings include the implementation of the Head of SMA Negeri 3 Kayuagung’s vision and mission regarding the development of students’ character, specifically the development of the character of scientific disciplines, as well as the principal’s strategy regarding the development of students’ character via accuracy, reprimand, motivation, environmental conditioning, habituation, and character integration through learning activities. The principal’s three main oversight responsibilities are to keep an eye on teachers as they teach students about character in the classroom, to supervise the progress of character education activity programs, to inspect the safety and integrity of school facilities, and to assess these activities through debriefing.